2021
DOI: 10.1016/j.xinn.2021.100164
|View full text |Cite
|
Sign up to set email alerts
|

Greenspace and human health: An umbrella review

Abstract: Multiple systematic reviews on greenspace and health outcomes exist, but the overall evidence base remains unclear. Therefore, we performed an umbrella review to collect and appraise all relevant systematic reviews of epidemiological studies on greenness exposure and health. We searched PubMed, Embase, and Web of Science from inception to June 28, 2021, and screened references of relevant articles. Systematic reviews with or without meta-analyses of epidemiological studies that examined the associations of gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 69 publications
1
78
0
Order By: Relevance
“…Recently, an increasing number of studies have indicated that greenness may lead to a wide range of beneficial health outcomes, such as those related to cardiovascular disease, mental health and birth weight. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Although some studies have reported a protective effect of greenness on birth weight, conclusions for the associations between greenness and PTB were inconsistent. 15 , 16 , 17 , 18 , 19 Some investigators have attempted to determine the association between greenness and PTB.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of studies have indicated that greenness may lead to a wide range of beneficial health outcomes, such as those related to cardiovascular disease, mental health and birth weight. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Although some studies have reported a protective effect of greenness on birth weight, conclusions for the associations between greenness and PTB were inconsistent. 15 , 16 , 17 , 18 , 19 Some investigators have attempted to determine the association between greenness and PTB.…”
Section: Introductionmentioning
confidence: 99%
“…In total, by 2022, more than 60 reviews and meta-analyses regarding nature and health and well-being had been conducted (cf. [ 22 ]).…”
Section: Introductionmentioning
confidence: 99%
“…There are some data that citizens’ physical health and well-being depend on the urban built neighborhood, which comprises both social and physical environments including green spaces [ 26 , 27 ]. It is assumed that green space is an important component of the health and well-being in urban areas [ 28 ]. Potential pathways linking green space to health comprise reducing exposure to air pollution, noise, physiological stress, and encouraging physical activity [ 29 ].…”
Section: Introductionmentioning
confidence: 99%